Peran Yayasan Insan Mulia Sejahtera Dalam Peningkatan Ekonomi Keluarga Melalui Budidaya Lele Bioflok Di Jakarta Selatan - Hajar Pramusutomo; Joned Ceilendra Saksana; T Ramli Zakaria (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2020)
Community empowerment is an activity that involves community participation. Community empowerment carried out by the Insan Mulia Sejahtera Foundation in South Jakarta through catfish farming business with the aim of improving the family economy, besides that it is also useful for improving family food security. This study aims to determine and analyze community empowerment carried out by Yayasan Insan Mulia Sejahtera through catfish cultivation biofloc system in the South Jakarta area. In addition, it is also to find out the supporting and inhibiting factors in the biofloc system catfish cultivation business. The method used in this study is a descriptive qualitative research method, with data collection techniques through interviews, observation and documentation, which are then analyzed and outlined in descriptive writing. The results showed that community empowerment implemented by Yayasan Insan Mulia Sejahtera has run well but has not been optimal, because there are still several obstacles or problems in its implementation. This is shown by the results of catfish cultivation have increased family economic income but have not been able to make catfish cultivation the main income of the family economy, or in other words just additional income for the family economy